KARAKTERISTIK GEOKIMIA AIR PANAS DAN ESTIMASI SUHU PERMUKAAN PANAS BUMI DI DAERAH SUOH KABUPATEN LAMPUNG BARAT PROVINSI LAMPUNG - Jasmin Arya Alfalah; Edy Sutriyono; M. Malik Ibrahim (LPPM Institut Pendidikan Nusantara Global, 2023)
Geochemical analysis is a method of geothermal exploration to determine the type of manifestation and estimate the temperature of the reservoir in the Suoh area and its surroundings. There are seven hot water sampling locations for physical observation and geochemical content tests, namely APS, APKSH, APKSC, APK1, APK2, APGS, and APBS. Geothermal manifestations in the Suoh area are on the path of the Sumatran fault system which is the result of a dextral-slip fault . If it is divided by segment, the Sumatran fault system in the study area is included in the Suoh segment, which in the Suoh segment, the fault line experiences a slight orientation and changes in tectonic activity, thus forming a transtension movement that works. The products of these forces result in movement apart and fractures forming a pull-apart basin opening . Based on the results of data processing using the geoindicator and water geothermometer methods, the results of plotting the Cl-SO4 -HCO3 diagram show that the seven hot water samples are the types of fluid types of chloride water and sulfuric acid water. Then the results of plotting the data using the Na-K-Mg diagram show that high Mg content indicates a process of dissolving ( leaching ) rocks near the surface and the results of water geothermometer calculations show that the average reservoir temperature ranges from 112-177 o C as a system temperature medium ( intermediate ). In the seven samples of hot water at the study site is a manifestation of geothermal fluid that comes directly from the reservoir.